ANALISIS PENGUASAAN KATA KERJA “TING SHUO” DAN “JU SHUO” PADA MAHASISWA 2016 BAHASA MANDARIN UNTAN - Meidia Dwi Cahyani; Lily Thamrin; Bun Yan Khiong (Universitas Tanjungpura, 2019)
AbstractVerbs are the most commonly used syntax in Chinese expressions. Verbs denote each action or action. Take the verbs